Functionalized gold nanorods (GNRs) as a label for the detection of thyroid-stimulating hormone (TSH) through lateral flow assay (LFA) - Varma, Sanjana; Burade, Dimpal K.; Chaudhari, Bhushan P. (Emergent Materials, 2025)
Thyroid-stimulating hormone (TSH) is an important biomarker of thyroid dysfunctions. Different types of nano biosensors have been developed to detect TSH. However, there is a lacuna in the development of sensitive paper-based nano biosensors due to less sensitivity and instability of the labels. Interestingly, the intense color and localized surface plasmon resonance (LSPR) property make gold nanorods (GNRs) an efficient lateral flow assay (LFA) label instead of spherical gold nanoparticles. The rapidity, simplicity and user-friendly functioning of LFAs make them a predominant technique compared to electrochemical techniques for point-of-care diagnosis. This proof-of-concept study underlines the role of stable GNRs as a novel label for LFAs. The TSH antibody functionalized GNRs can semi-quantitatively diagnose hyperthyroidism and hypothyroidism. The limit of detection (LOD) of the LFA is 0.3 µIU/mL, determined by visually analyzing the color development at the test line without employing any quantification method. Moreover, the study provides a comprehensive understanding of seed-mediated synthesis and functionalization of GNRs, which would benefit the researchers in suitably designing the GNRs-based labels for LFAs. Considering their exceptional characteristics, GNR-based LFAs are expected to surpass other labelling nanomaterials in detecting various biological markers. This enhanced sensitivity could significantly improve the clinical utility of diagnostic kits.

Understanding the antimicrobial and antioxidant potential of bioinspired platinum nanoparticles synthesized using ocimum tenuiflorum - Varma, Sanjana; Bamb, Aagam Lalit; Tambe, Sayali A.; Burade, Dimpal K.; Jagdale, Swati; Pande, Bharat; Vamkudoth, Koteswara Rao; Chaudhari, Bhushan P. (BioNanoScience, 2025)
The emergence of infectious diseases has highlighted the need for novel and effective antimicrobial agents. Platinum nanoparticles (PtNPs) could act as a potent antimicrobial agent due to their unique physicochemical properties. However, the chemical or physical synthesis methods of PtNPs have drawbacks, like irregular shape and use of toxic chemicals. These drawbacks can be effectively overcome by using the biological method synthesis. Thus, this study presents the green synthesis of platinum nanoparticles (PtNPs) using Ocimum tenuiflorum leaf extract as a bio-reductant. The study also comprehensively encompasses the role of multiple process parameters for the green synthesis of PtNPs. The high-resolution transmission electron microscopy (HR-TEM) revealed spherical PtNPs with an average size of 2.36 ± 0.5 nm that exhibits excellent stability (zeta potential, −45.67 ± 2.57 mV). Phytochemical analysis of aqueous O. tenuiflorum leaf extract was performed to assess the bioactive compounds like saponins, phenols, and tannins, reducing sugars and flavonoids. The PtNPs demonstrated significant antioxidant activity of 86.9 ± 0.12% at 10 µg/mL. Further, the biosynthesized PtNPs showed efficient antimicrobial activity with a minimum inhibitory concentration (MIC) of 6.25 µg/mL against Escherichia coli and 1.5 µg/mL against Staphylococcus aureus. These findings highlight the therapeutic potential of eco-friendly PtNPs for pharmaceutical and biotechnological applications.